Scalable extracellular expression of tag-free MPT64 protein in E. coli via pelB signal optimization: a step toward tuberculosis diagnostic antigen preparation - Kusuma, Sri Agung Fitri; Fatinah, Yasmin; Fadhlillah, Muhammad; Parwati, Ida; Rukayadi, Yaya; Subroto, Toto (Taylor and Francis, 2025)
Tuberculosis (TB) remains a global health burden, requiring affordable and scalable diagnostic tools. The MPT64 protein is a secreted biomarker specific to Mycobacterium tuberculosis and holds promise for rapid antigen-based diagnostics. However, existing recombinant expression systems often yield low extracellular amounts, complicating purification and limiting downstream application. This study aimed to optimize the extracellular, tag-free expression of MPT64 protein in Escherichia coli by employing the pelB signal peptide in combination with Response Surface Methodology (RSM). A Box-Behnken design was used to analyze the interactive effects of rhamnose concentration, induction timing, and medium composition. The optimal condition (4 mM rhamnose, 2-h induction, and 1.8-fold medium enrichment) yielded 0.0293 mg/mL of extracellular MPT64. The identity and antigenicity of the secreted protein were validated using Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) and lateral flow immunoassay (LFIA), respectively. This study demonstrates that fine-tuning expression parameters can significantly enhance extracellular protein yield, providing a cost-effective production strategy for MPT64-based TB diagnostics and laying the foundation for future scalable diagnostic development.